2021
DOI: 10.1038/s41467-021-26654-5
|View full text |Cite
|
Sign up to set email alerts
|

Diet composition influences the metabolic benefits of short cycles of very low caloric intake

Abstract: Diet composition, calories, and fasting times contribute to the maintenance of health. However, the impact of very low-calorie intake (VLCI) achieved with either standard laboratory chow (SD) or a plant-based fasting mimicking diet (FMD) is not fully understood. Here, using middle-aged male mice we show that 5 months of short 4:10 VLCI cycles lead to decreases in both fat and lean mass, accompanied by improved physical performance and glucoregulation, and greater metabolic flexibility independent of diet compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 55 publications
1
14
0
Order By: Relevance
“…There are interesting sex-specific effects of TRF benefits, reflecting differences in the innate response to high-fat-diet feeding and adding to the growing evidence across aging studies that females are not the same as males. Thus, the impact of nutrient limitation by CR and the effect of TRF on health indices is observed whether animals are on standard diets or on high-fat diets, although the specifics of the metabolic reprograming are not identical (Diaz-Ruiz et al, 2021). It seems that the context matters, perhaps reflecting the importance of metabolic status, and the best strategy to harness health-and longevity-associated pathways that may be different when starting from a metabolically compromised position.…”
Section: Intermittent Fastingmentioning
confidence: 99%
“…There are interesting sex-specific effects of TRF benefits, reflecting differences in the innate response to high-fat-diet feeding and adding to the growing evidence across aging studies that females are not the same as males. Thus, the impact of nutrient limitation by CR and the effect of TRF on health indices is observed whether animals are on standard diets or on high-fat diets, although the specifics of the metabolic reprograming are not identical (Diaz-Ruiz et al, 2021). It seems that the context matters, perhaps reflecting the importance of metabolic status, and the best strategy to harness health-and longevity-associated pathways that may be different when starting from a metabolically compromised position.…”
Section: Intermittent Fastingmentioning
confidence: 99%
“…Liraglutide mimicked caloric restriction in mice, resulting in dramatic anorexia and weight loss in our study and others ( 20 , 21 , 36 ). Several metabolomic studies on caloric restriction using a very low-calorie diet, a fasting-mimicking diet, or fasting identified metabolomic signatures in the serum and liver ( 62 , 63 , 64 , 65 , 66 , 67 , 68 ). Caloric restrictions using these diets or acute fasting markedly increased 3-hydroxybutyric acid, a ketone body, in the serum and liver of both NCD and HFD mice ( 62 , 63 , 64 , 65 , 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several metabolomic studies on caloric restriction using a very low-calorie diet, a fasting-mimicking diet, or fasting identified metabolomic signatures in the serum and liver ( 62 , 63 , 64 , 65 , 66 , 67 , 68 ). Caloric restrictions using these diets or acute fasting markedly increased 3-hydroxybutyric acid, a ketone body, in the serum and liver of both NCD and HFD mice ( 62 , 63 , 64 , 65 , 66 ). Interestingly, our data showed that liraglutide increased 3-hydroxybutyric acid in the liver but not in the plasma of HFD mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caloric restriction has been demonstrated to be associated with improvement in physical endurance, blood pressure, heart-rate variability, and glucose metabolism. 3 , 4 , 5 , 6 , 7 , 8 This review will focus on the potential role of stem cells in mediating the benefits of decreased caloric intake in prevention of atherosclerotic disease.…”
Section: Upavasa and Vascular Endotheliummentioning
confidence: 99%